2008
DOI: 10.1186/1471-2466-8-22
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long time survival after lung cancer surgery: A retrospective cohort study

Abstract: Background: There have been few reports regarding long time survival after lung cancer surgery. The influence of age and pulmonary function on long time survival is still not fully discovered. Some reports suggest that hospitals with a high surgical volume have better results. The aim of this study was to evaluate lung cancer surgery performed in a county hospital in terms of 30 days mortality, complications and predictors of long time survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
4
13
0
1
Order By: Relevance
“…Socioeconomic factors could possibly influence referral patterns (26), but are not likely of importance in our country where treatment for cancer is free for all patients. Previous studies from west Norway of the 5‐year survival rate after surgical treatment reported estimates of 46% (27) and 41% (28), which correspond with the 5‐year survival rate of 51% in the operated patients in our cohort.…”
Section: Discussionsupporting
confidence: 82%
“…Socioeconomic factors could possibly influence referral patterns (26), but are not likely of importance in our country where treatment for cancer is free for all patients. Previous studies from west Norway of the 5‐year survival rate after surgical treatment reported estimates of 46% (27) and 41% (28), which correspond with the 5‐year survival rate of 51% in the operated patients in our cohort.…”
Section: Discussionsupporting
confidence: 82%
“…The overall five-year survival in lung cancer has not changed markedly in Norway the last 40 years (figure 1), but a trend in the last years of a moderate increase in survival in women is observed (5). In a recent study from Norway female gender was a predictor for long time survival in a selected population of lung cancer patients offered surgery (100). We have found 17 clinical lung cancer studies from Norway published in the last 10 years (table 10a+10b), and we want to discuss their observations in the context of lung cancer patients at Haugalandet.…”
Section: Paper IIImentioning
confidence: 95%
“…Dette er i motsetning til en annen norsk studie hvor FEV 1 < 80 % predikerte redusert langtidsoverlevelse (13). I vår studie kan fravaer av en slik sammenheng skyldes seleksjon, ved at pasienter med uttalt komorbiditet og dår-lig lungefunksjon i større grad ble ekskludert fra kirurgisk behandling i denne tidsperioden.…”
Section: Operasjonsmortalitet Og Residivunclassified